The League of Unexceptional Children : Get smart-ish - Daneshvari, Gitty (League of Unexceptional Children, 2016)
"Utterly average twelve-year-olds Jonathan Murray and Shelley Brown, agents with the League of Unexceptional Children, travel to the United Kingdom to help MI5 capture a rogue teenage spy"--